Motor imagery difficulties in children with Cerebral Palsy: A specific or general deficit?. (October 2016) - Lust, Jessica M.; Wilson, Peter H.; Steenbergen, Bert
Highlights: This paper presents the first study to compare explicit and implicit MI ability in the same group of children with CP. Deficits in MI that are specific to the implicit mode of control are highlighted in children with CP. Results suggest that children with CP may benefit from rehabilitation techniques that utilize the explicit forms of MI. Abstract: Aim: The aim of this study was to examine the specificity of motor imagery (MI) difficulties in children with CP. Method: Performance of 22 children with CP was compared to a gender and age matched control group. MI ability was measured with the Hand Laterality Judgment (HLJ) task, examining specifically the direction of rotation (DOR) effect, and the Praxis Imagery Questionnaire (PIQ). Results: In the back view condition of the HLJ task both groups used MI, as evidenced by longer response times for lateral compared with medial rotational angles. In the palm view condition children with CP did not show an effect of DOR, unlike controls. Error scores did not differ between groups. Both groups performed well on the PIQ, with no significant difference between them in response pattern. Conclusion and implication: The present study suggests that children with CP show deficits on tasks that trigger implicit use of MI, whereas explicit MI ability was relatively preserved, as assessed using the PIQ. These results suggest that employing more explicit methods of MI training may well be more suitable for children with CP in rehabilitation of motor function.